The PEA3 Subfamily of Ets Transcription Factors Synergizes with β-Catenin–LEF-1 To Activate Matrilysin Transcription in Intestinal Tumors - Crawford, Howard C. (American Society for Microbiology, 2001)
The matrix metalloproteinase matrilysin (MMP-7) is expressed in the tumor cells of a majority of mouse intestinal and human colonic adenomas. We showed previously that matrilysin is a target gene of β-catenin–Tcf, the transcription factor complex whose activity is thought to play a crucial role in the initiation of intestinal tumorigenesis. Here we report that overexpression of a stable mutant form of β-catenin alone was not sufficient to effect expression of luciferase from a matrilysin promoter-luciferase reporter plasmid. However, cotransfection of the reporter with an expression vector encoding the PEA3 Ets transcription factor, or its close relatives ER81 and ERM, increased luciferase expression and rendered the promoter responsive to β-catenin–LEF-1 as well as to the AP-1 protein c-Jun. Other Ets proteins could not substitute for the PEA3 subfamily. Luciferase activity was induced up to 250-fold when PEA3, c-Jun, β-catenin, and LEF-1 were coexpressed. This combination of transcription factors was also sufficient to induce expression of the endogenous matrilysin gene. Furthermore, all matrilysin-expressing benign intestinal tumors of the Min mouse expressed a member of the PEA3 subfamily, as did all human colon tumor cell lines examined. These data suggest that the expression of members of the PEA3 subfamily, in conjunction with the accumulation of β-catenin in these tumors, leads to coordinate upregulation of matrilysin gene transcription, contributing to gastrointestinal tumorigenesis.